2021
DOI: 10.21037/apm-20-2328
|View full text |Cite
|
Sign up to set email alerts
|

Controlling nutritional status is a prognostic factor for patients with lung cancer: a systematic review and meta-analysis

Abstract: Background: Nowadays, controlling nutritional status (CONUT) has been used as a prognostic factor in variety of cancers. However, no consensus has been reached on the prognostic value of CONUT in lung cancer. In this study, we aim to investigate the role of CONUT in survival of patients with lung cancer.Methods: EMBASE, web of science, and Medline were used to search articles in English-language journals.The association between CONUT score and survival of patients with lung cancer was evaluated by using pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…And through the prognostic survival curve, we could see that the increase of miR-18a-5p and the decrease of ATM after treatment both predict an increased risk of prognostic death of patients, which was further verified by the subsequent COX analysis of the prognosis of patients, demonstrating the close relationship between miR-18a-5p, ATM, and the development of ESCC. TNM staging and lymph node metastasis, as the basis for the pathological development of tumor diseases, can naturally be expected to be related to the prognosis of ESCC [ 37 , 38 ], so this article will not go into details. The above results also suggested that miR-18a-5p and ATM may also be potential therapeutic targets for ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…And through the prognostic survival curve, we could see that the increase of miR-18a-5p and the decrease of ATM after treatment both predict an increased risk of prognostic death of patients, which was further verified by the subsequent COX analysis of the prognosis of patients, demonstrating the close relationship between miR-18a-5p, ATM, and the development of ESCC. TNM staging and lymph node metastasis, as the basis for the pathological development of tumor diseases, can naturally be expected to be related to the prognosis of ESCC [ 37 , 38 ], so this article will not go into details. The above results also suggested that miR-18a-5p and ATM may also be potential therapeutic targets for ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Several tools for assessing nutritional status have been developed, including the Geriatric Nutritional Risk Index (GNRI), Prognostic Nutritional Index (PNI), Controlling Nutritional Status (CONUT) score, and Mini Nutritional Assessment (MNA). These nutritional assessment tools showed prognostic value in patients with malignancy, CAD, heart failure and, peripheral arterial diseases ( 8 , 9 , 11 , 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The controlling Nutritional Status (CONUT) score has been reported to be a simple and efficient screening tool for evaluating malnutrition status, especially for early detection and ongoing monitoring of nutritional status in hospitalized patients ( 16 ). Current studies suggest that CONUT is associated with short- and long-term prognoses in some diseases ( 9 , 14 , 15 , 17 ). The CONUT score is calculated based on the parameters of serum albumin, total cholesterol and, total lymphocyte levels, consisting of an immune-nutritional index reflecting protein/lipid metabolism and immunocompetence ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Controlling Nutritional Status (CONUT) score is a nutritional scoring tool that is calculated using serum albumin, total cholesterol level, and total lymphocyte count (7). Current studies suggest that CONUT is associated with short-and long-term prognoses in some diseases, particularly cancers (8)(9)(10)(11)(12)(13)(14). However, the predictive role of the CONUT score for in-hospital mortality in older adult inpatients has not been clearly established.…”
Section: Introductionmentioning
confidence: 99%